Protective role of human beta-defensin-2 and cathelicidin in high risk close household contacts of pulmonary tuberculosis - Sudhasini Panda; Shah Faisal; Diravya M Seelan; Manisha Dagar; Lokesh Mandlecha; Vidushi Varshney; Mridul Sharma; Kalpana Luthra; Neeraj Kumar Gupta; Archana Singh (Clinical Immunology Communications, 2023)
Host-defense peptides (HDPs) such as human beta-defensin-2 (hBD-2) and cathelicidin (LL37) are essential components of innate immune response against tuberculosis (TB) infection, which could also be assessed for diagnostic potential in spectrum of TB infection. We assessed mRNA and circulating levels of HDPs in pulmonary TB (PTB) patients and their household contacts (HHCs). hBD-2 and LL37 were found to be significantly higher in both PTB and HHCs suggestive of bacterial exposure which was further corroborated by higher levels of HDPs in mantoux positive HHCs (latent TB). Higher levels of HDPs in HHCs may suggest protective host response against infection as indicated by inverse relation of LL37 with disease severity in PTB. Both peptides demonstrated high levels of sensitivity and specificity, although hBD-2 proved to be a better HDP for distinguishing LTBI from active TB at a cutoff of 3904 pg/ml. However, follow-up studies are required to validate these findings.